MEMBANGUN MODAL SOSIAL MELALUI CREDIT UNION (Studi Kasus Credit Union Unggul Sejahtera di Desa Kendel, Kecamatan Kemusu, Kabupaten Boyolali, Provinsi Jawa Tengah) - Benny Kurniawan; Daru Purnomo (Universitas Kristen Satya Wacana, 2013)
Kendel is a name village of Boyolali district has capable preserving kejawen culture. Cultural capital is elements of social capital, that is the thinking behind their researchers to conduct when Credit Union Unggul Sejahtera (CUUS) present to help manage economy for their area. The purpose of research to explained about the role of social capital to make benefit socio-economic members of CUUS. Types and approaches of research is descriptive to explained CUUS as a means learning of social capital. Analysis using a qualitative approach non probability sampling. Unit of analysis is the Credit Union Unggul Sejahtera (CUUS). The observation unit members and administrators of CUUS in Kendel village. From the research that Rapat Anggota Tahunan (RAT) leads to depotism for the benefit of local economic development. Violent symbolic representations that are performed the management of very helpful when solve problems CUUS. Kendel have capital social sufficient to conducting activities CUUS through kejawen the value of cultural and islamist, so that capital strong social developed toward which aims to salary through CUUS.From the research it can be concluded money used as a new social capital in order to maintain trust between individuals. CUUS could develop human capital through the results of stimulus funds awarded to members with business activities of snacks. Members can put aside money as needed so that it is easier to manage finance is a result of new habitus. Background to make the interaction more based on the reciprocity of the interaction process based on three pillars CUUS, education, independent, and solidarity. Keywords: Social Capital, New Habitus, CUUS, Human Capital.